Makna Alasan-Alasan Tertentu dalam Kode Etik Notrais Terkait Kewajiban Menjalankan Jabatan Notaris di Kantornya - Ramadhan, Ajeng Fitrah; Permadi, Iwan (Universitas Negeri Malang, 2019)
This paper aims to analyze the meaning of “certain reasons” in Article 3 Paragraph 15 of the Notary Ethics Code about the obligation to carry out his position in the office and the consequences of violating these provisions against the authenticity of the deed. This study uses the normative juridical method with the statute approach and conceptual approach. The results of the study indicate that the meaning of “certain reasons” referred to Article 3 Paragraph 15 of the Notary Ethics Code is the reasons permitted by the Law, namely related to the making of a deed that is not possible to be carried out in a notary’s office. The deed is authentic if in making it does not violate one of the terms of authenticity of the notary deed even though the notary violates the provisions of Article 3 Paragraph 15.